Confront A Nation's Fear Of Prince Albert In Tom Hooper's King's Speech Movie (2010): An Individual Psychological Approach - Anggraini, Lany, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S., M.Hum (2013)
This study is aimed to show the search the notion's fear of Prince Albert in King's Speech movie (2010) using individual psychological approach. It is done by establishing two objectives; the first analyzing the movie based on individual psychological analysis. This research is descriptive qualitative research. The primary data taken from a movie entitled King's Speech which was released in 2010 directed by Tom Hooper and the secondary data source is including the script of the movie and the other information taken from the book and the website from internet that were relevant to the subject matter. The study comes to following conclusions. First based on the structural analysis, the director, Tom Hooper adapted and built his movie employing the right mise-en-scene and proper cinematography so that the movie formed a good unity to deliver a moral message that perseverance and friendship can lead to success. Secondly, the individual psychological approach is used to analyze the notion of fear of Prince Albert.